1993
DOI: 10.1002/jbm.820271214
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phagocytosis of poly(L‐lactic acid) fragments on cellular morphology and viability

Abstract: The aim of this study was to investigate the effect of phagocytosed poly(L-lactic acid) particles on the morphology and viability of phagocytes, mainly macrophages. Therefore, predegraded poly(L-lactic acid) (P-PLLA) and nontreated PLLA (N-PLLA) particles, both having diameters not exceeding 38 microns, were injected intraperitoneally in mice. P-PLLA particles were obtained by 25 kGy gamma-irradiation of N-PLLA particles. N-PLLA and P-PLLA particles were injected using an 0.3% ethanol/0.9% saline solution intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
2
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 23 publications
(1 reference statement)
1
49
2
4
Order By: Relevance
“…This work was supported by grants from PIBIC/CEPE (Programa Institucional de Bolsas de Iniciação Científica -Conselho de Ensino Pesquisa e Extensão). response [28][29][30][31] . Foreign body giant multinuclear cells are small phagocytes that possess a large number of lysosomes and high respiratory enzymatic activity.…”
Section: Resultsmentioning
confidence: 99%
“…This work was supported by grants from PIBIC/CEPE (Programa Institucional de Bolsas de Iniciação Científica -Conselho de Ensino Pesquisa e Extensão). response [28][29][30][31] . Foreign body giant multinuclear cells are small phagocytes that possess a large number of lysosomes and high respiratory enzymatic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Liposomes and solid lipid particles have intrinsically poor chemical stability and are degraded by serum (16), thereby decreasing drug delivery to the target cells while increasing potential systemic toxicity. There is also concern that macrophage uptake of biodegradable polymer-based nanoparticles (such as poly-L-lactide and PLGA) may cause cell damage, cytokine release, and inflammation (24,32,42), although evidence of their benign nature and lack of associated histopathology has also been reported (11,41). In contrast to these potential problems with liposomal and biodegradable polymer delivery systems, preliminary in vivo experiments have found enhanced blood stability of MSNP compared with liposomes and polymeric nanoparticles (4) and have demonstrated favorable biocompatibility, biodegradation and excretion properties (18,29,45).…”
mentioning
confidence: 99%
“…It was reported that, after the PLLA segments were swallowed in vivo by phagocytes, cell damage and cell death were obvious. The highest numbers of necrotic cells were observed on day 2 [154]. These reactions can result in an unexpected risk for patients and have strongly limited in clinical applications of this kind of biomaterials.…”
Section: Polyglycolide (Pga) Polylactide (Pla) and Poly(lactic-co-glmentioning
confidence: 99%